Treating crop-raiding elephants with aspirin - Barnes, Richard (Pachyderm, 2002)
In this opinion piece the author notes 'Most attempts to tackle cases of elephant crop raiding are searches for an effective palliative - an aspirin for that particular situation.' He suggests that the elephants (of course unless they are eliminated) will always return unless a long-term solution is found by addressing the underlying causes in the particular instance. Reviews the concept of carrying capacity for elephants, the reality of landscape modification, and the propensity to adopt short term solutions. Concludes with a discussion of the facts behind crop raiding by elephants, and the root causes of the present land use conflict between human, particularly agriculturalists, and elephant populations.